High-Salinity Fluid Downslope Flow on Regolith Layer Examined by Laboratory Experiment: Implications for Recurring Slope Lineae on Martian Surfaces - Yoshiki Tabuchi; Arata Kioka; Takeshi Tsuji; Yasuhiro Yamada (Fluids)
Numerous dark linear recurrent features called Recurring Slope Lineae (RSL) are observed on Martian surfaces, hypothesized as footprints of high-salinity liquid flow. This paper experimentally examined this “wet hypothesis” by analyzing the aspect ratios (length/width) of the flow traces on the granular material column to investigate how they vary with the granular material column, liquid and its flow rate, and inclination. While pure water produced low aspect ratios (<1.0) on the Martian regolith simulant column, high-salinity fluid (CaCl2(aq)) traces exhibited significantly higher aspect ratios (>4.0), suggesting that pure water alone is insufficient to explain RSL formulation. Furthermore, the aspect ratios of high-salinity fluid traces on Martian regolith simulants were among the highest observed across all studied granular materials with similar particle sizes, aligning closely with actual RSL observed on Martian slopes. The results further suggest that variable ARs of actual RSL at the given slope can partly be explained by variable flow rates of high-salinity flow as well as salinity (i.e., viscosity) of flow. The results can be attributed to the unique granular properties of Martian regolith, characterized by the lowest permeability and Beavers–Joseph slip coefficient among the studied granular materials. This distinctive microstructure surface promotes surface flow over Darcy flow within the regolith column, leading to a narrow and long-distance feature with high aspect ratios observed in Martian RSL. Thus, our findings support that high-salinity flows are the primary driver behind RSL formation on Mars. Our study suggests the presence of salts on the Martian surface and paves the way for further investigation into RSL formulation processes.